Pengaruh Citra Merek, Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian Paket Premium Pada Aplikasi Music Streaming Spotify - Suharyono Suharyono; Ajeng Suasti Astuti (Neolectura, 2020)
Digitalization in every industry continues to develop, which is also happened to the music industry. Music streaming applications are a technology that is in great demand today. Spotify is an on-demand music service application that is popular among music lovers. Spotify offers a free package and paid (premium) package services. The difference between the two service models lies in the quality and different service features. The purpose of this thesis is to analyze the influence of brand image, product quality, price, and promotion on premium package purchase decisions on the Spotify music streaming application. Research data obtained by survey method using a questionnaire. With a sample of 100 respondents. The analysis technique used is Structural Equation Modeling (SEM) using the AMOS 22 program. The results of this study showed that brand image, product quality, price, and promotion simultaneously have a positive effect on purchasing decision. Then brand image and product quality variables partially have a positive and significant effect on purchasing decisions, evidenced by the value of each CR is greater than 1.96 (CR> 1.96) and the significance value is smaller than 0.05 (P <0.05).